Revisiting relationship between Malaysian Stock Market Index and selected macroeconomic variables using asymmetric cointegration - Hakimah Nur Ahmad Hamidi,; Norlin Khalid,; Zulkefly Abdul Karim, (Penerbit Universiti Kebangsaan Malaysia, 2018)
This article re-examines the relationship of several macroeconomics variables with Malaysia Stock Market Index, KLCI. The paper applies Johansen (1988) procedure and vector error correction model (VECM) for symmetric cointegration, while threshold cointegration test proposed by Enders and Siklos (2001) is used for asymmetric cointegration. Using quarterly time series data set spanning from 1990 to 2015, the findings show the presence of the long-run relationship between KLCI and the macroeconomics variable i.e., industrial production index, inflation rate, exchange rate and money supply. We also found evidence for asymmetric adjustment of the stock price index towards its long-run values. These results have particularly important policy implications, concerning the formulation of macroeconomic policy to achieve financial stability and thus contribute to the further development of Malaysian Stock Market Index.